2019
DOI: 10.1039/c8gc03695k
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating bioplastic production with light energy by couplingRalstonia eutrophawith the photocatalyst graphitic carbon nitride

Abstract: The photocatalyst g-C3N4 provides visible light-derived energy to Ralstonia eutropha and improves 1.4 times the heterotrophic production of polyhydroxybutyrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 72 publications
0
39
0
1
Order By: Relevance
“…It has been reported that the non-metal graphitic carbon nitride (g-C 3 N 4 ) has been combined with Ralstonia eutropha for bioplastic production under light irradiation (Xu et al, 2019). This proof-of-concept study illustrated that the inorganic photocatalysts could also enhance the productivity of the cellbased hybrid system with good biological compatibility.…”
Section: Introductionmentioning
confidence: 79%
“…It has been reported that the non-metal graphitic carbon nitride (g-C 3 N 4 ) has been combined with Ralstonia eutropha for bioplastic production under light irradiation (Xu et al, 2019). This proof-of-concept study illustrated that the inorganic photocatalysts could also enhance the productivity of the cellbased hybrid system with good biological compatibility.…”
Section: Introductionmentioning
confidence: 79%
“…In the absence of any sacrificial electron donor, R. eutropha-g-C 3 N 4 improved the PHB production by 1.2 times and with triethanolamine as an electron donor, the production was enhanced by 1.4 times compared with pure R. eutropha. Furthermore, the ratio of intracellular reductase NADPH/NADP was increased in the hybrid system due to facile energy metabolism [68]. Tremblay and collogues further improved the PHB production potential of R. eutropha-g-C 3 N 4 by coupling g-C 3 N 4 with H 2 O 2 -degrading catalase [69].…”
Section: Nps For Photosensitizationmentioning
confidence: 99%
“…In the same year, a living quantum dot (QD) bacterial hybrid was constructed through the self-assembly of biocompatible QD and specific enzymes inside the living cells [62]. See [30][31][32]41,[52][53][54][55][56]63,68,70]. efficiency in CO 2 photoreduction is to combine inorganic and biological systems as hybrid systems.…”
Section: Self-photosensitized Microbial Systemsmentioning
confidence: 99%
“…23,24 These use non-enzymatic photocatalysts which exhibit high solar-to-chemical energy conversion 24 and have shown biocompatibility with various microorganisms. 25 Seminal studies from Torella and coworkers and Liu and co-workers demonstrated the use of bioelectrochemical cells containing R. eutropha to produce PHB and fusal alcohols from CO 2 and H 2 O. 26,27 Using a reactive oxygen species (ROS)-resistant Co-P alloy cathode, the authors achieved CO 2 reduction efficiencies exceeding that of natural photosynthesis.…”
Section: Harnessing Microbial Chemistry For Solar Light Driven Reactionsmentioning
confidence: 99%